1994
DOI: 10.1136/oem.51.8.557
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema and airway obstruction in non-smoking South African gold miners with long exposure to silica dust.

Abstract: Objective-Occupational exposure to silica dust is associated with significant impairment oflung function. The present study investigates which pathological changes in the lung are associated with impairment oflung function in silica dust exposed workers who were life-long nonsmokers. Methods-242 South African white gold miners who were lifelong non-smokers and who had a necropsy at death were studied. The pathological features identified at necropsy were the degree and type of emphysema, the presence of airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 10 publications
0
22
0
3
Order By: Relevance
“…As with the studies of airway obstruction and coal mining, the studies on gold mining have the inherent challenge of disentangling the restrictive deficits associated with the dust exposure from obstructive deficits. The dust exposure with high silica concentration has been associated with different respiratory health outcomes: asthma (23), bronchial hyper-responsiveness (24), emphysema (25), silicosisassociated dysfunction, chronic airflow limitation, and chronic bronchitis (26), and studies among gold miners have found loss in lung function associated with pulmonary tuberculosis (27). The diversity in respiratory health outcome associated with the same exposure pinpoints a diagnostic uncertainty.…”
Section: Studies Of Airway Obstruction Not Included In the Systematicmentioning
confidence: 99%
“…As with the studies of airway obstruction and coal mining, the studies on gold mining have the inherent challenge of disentangling the restrictive deficits associated with the dust exposure from obstructive deficits. The dust exposure with high silica concentration has been associated with different respiratory health outcomes: asthma (23), bronchial hyper-responsiveness (24), emphysema (25), silicosisassociated dysfunction, chronic airflow limitation, and chronic bronchitis (26), and studies among gold miners have found loss in lung function associated with pulmonary tuberculosis (27). The diversity in respiratory health outcome associated with the same exposure pinpoints a diagnostic uncertainty.…”
Section: Studies Of Airway Obstruction Not Included In the Systematicmentioning
confidence: 99%
“…(31,32,33) A NIOSH evaluation at this same plant in 1979 found that 7 (27%) of 26 participating current and former workers with one or more years exposure had chest x-ray changes consistent with silicosis. (34) Three cases were identified among 15 current workers and four cases were identified among 11 former workers.…”
Section: Discussionmentioning
confidence: 99%
“…(25)(26) As alterações clínicas e funcionais observadas, embora guardem certa relação com as alterações radiográficas, podem ser encontradas em indiví-duos expostos sem evidências radiográficas de silicose.…”
Section: Limitação Crônica Ao Fluxo Aéreo E Câncer Pulmonarunclassified